Sistem Informasi Akademik Pada Sekolah Tinggi Ilmu Sosial Dan Ilmu Politik Silas Papare Jayapura - Mayor, Perskilla Risa Linda; Jusmawati, J; Robo, Salahudin (STIKOM Tunas Bangsa Pematangsiantar, 2021)
School of Silas Papare Jayapura is one of the high schools that has implemented an information system in carrying out their management of job. However, there are still lack in the application of the information system. As in the academic section, the information system has not been implemented in managing lecture activities, so that the data management of activities in the academic section are still carried out semi-manually. The purpose of this research is to assist academic staff in managing academic data, assist lecturers in inputing of score, and provide better service for students of Silas Papare Jayapura. This web-based Academic Information System was created using the PIECES analysis method, using the Unified Modeling Language (UML) method as a system design, using the waterfall method as a system development, and the Black Box as system testing method. This research produces an academic information system that has been organized in managing academic data and becomes a means of information systems for academics, lecturers and students in schools of Silas Papare Jayapura